Mukhalinga on double chaitya arch on the exterior wall of garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The side walls of the garbhagriha have windows which are topped by double chaitya arches. The lower chaitya arch depicts the bust of a deity flanked by two celestial beings. The upper chaitya arch shows a grassamukha.